The Effect Of Work Motivation On The Performance Of Libraries In The Library Of The State Islamic University Of North Sumatera (UINSU) Medan - Matondang, Mutiara Ramadhani; Irwansyah; Sumanti, Solihah Titin (Pena Cendekia Insani, 2022)
Librarian work motivation is the main factor that can support the librarian's high and low performance. Librarian can be said to have a high performance if he likes the job done, has high motivation and is able to solve problems well. This is what motivates the author to further investigate whether there is an influence between work motivation on the performance of librarians at the UIN North Sumatra Library. The purpose of this study was to determine whether there was an effect of work motivation on the performance of librarians at the UIN North Sumatra Library. In connection with that, the approach taken is the theories related to work motivation and performance of librarians. This type of research is descriptive correlational with a quantitative approach. Methods of data collection using observation, questionnaires and documentation. The data analysis used was a descriptive statistical analysis and simple linear regression analysis. Data processing was carried out with the help of SPSS 20 software. The results of this study indicate that work motivation affects the Librarian Performance of UIN North Sumatra.